2021
DOI: 10.1111/coa.13794
|View full text |Cite
|
Sign up to set email alerts
|

The immunotherapeutic role of indoleamine 2,3‐dioxygenase in head and neck squamous cell carcinoma: A systematic review

Abstract: Background Novel cancer immunotherapy seeks to harness the body's own immune system and tip the balance in favour of antitumour activity. The intracellular enzyme indoleamine 2,3‐dioxygenase (IDO) is a critical regulator of the tumour microenvironment (TME) via tryptophan metabolism. The potential immunotherapeutic role of IDO in head and neck squamous cell carcinoma (HNSCC) requires further exploration. We aim to assess the evidence on IDO in HNSCC. Methods A systematic review of literature and clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 85 publications
(150 reference statements)
1
10
0
Order By: Relevance
“…Friberget et al first reported the IDO1 pathway as a possible tumor immune escape mechanism in 2002 when they observed IDO1 expression by monocytes in tumor tissues and tumor-draining lymph nodes [ 67 ]. In the past decade, numerous studies have observed high IDO1 levels in human tumors, including glioblastoma, head and neck squamous cell carcinoma, breast cancer adrenocortical carcinoma, esophageal squamous cell carcinoma, gastric cancer, and colon cancer [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Role Of Ido1 In Tmementioning
confidence: 99%
“…Friberget et al first reported the IDO1 pathway as a possible tumor immune escape mechanism in 2002 when they observed IDO1 expression by monocytes in tumor tissues and tumor-draining lymph nodes [ 67 ]. In the past decade, numerous studies have observed high IDO1 levels in human tumors, including glioblastoma, head and neck squamous cell carcinoma, breast cancer adrenocortical carcinoma, esophageal squamous cell carcinoma, gastric cancer, and colon cancer [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Role Of Ido1 In Tmementioning
confidence: 99%
“…They prevent ligand–receptor engagement, avoiding diseases such as autoimmune ones. Its applicability in the treatment of malignancies such as cancer has greatly improved the survival of patients and has been revolutionizing the field of cancer treatment [ 14 ].…”
Section: Targeting Icsmentioning
confidence: 99%
“…Later on, the outcome of patients improved with the emergence of mAbs targeting the axis of PD-1/PD-L1. Currently, there are seven different IC inhibitors that have been approved for the treatment of patients as first- and second-line therapies [ 13 , 14 , 37 ]; however, there is a subset of individuals that still do not respond to this therapy by presenting de novo and/or adaptive responses [ 14 , 15 , 16 , 17 , 18 , 38 ]. For instance, treatment targeting anti-PD-1/PD-L1 therapy in certain types of cancers with microsatellite stability shows poor efficiency [ 39 ].…”
Section: Targeting Icsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, other immunotherapies that can modify the immune landscape of the tumor to enhance the effect of existing ICIs should be identified (11)(12)(13). A promising target molecule may be indoleamine 2,3-dioxygenase 1 (IDO1), a cytosolic heme-containing enzyme that catalyzes the initial step of tryptophan catabolism kynurenine and its other immunosuppressive catabolites (14). At present, the two most advanced and investigated drugs for IDO1 inhibition are indoximod and epacadostat (13).…”
Section: Introductionmentioning
confidence: 99%